Synchronization in pairs of rotating active biomotors. Issue 16 (17th April 2018) - Oliver, Neus; Alpmann, Christina; Barroso, Álvaro; Dewenter, Lena; Woerdemann, Mike; Denz, Cornelia
Abstract : The emergence of synchronization between pairs of rotating bacteria is investigated as a function of the coupling strength, i.e. separation distance. Abstract : Although synchronization is a well-known physical phenomenon, experimental studies of its emergence in living bacterial cells are still scarce. The difficulty in generating a controlled scenario to detect synchronization has limited the experimental outcomes so far. We present a realization based on holographic optical tweezers in which adhered pairs of self-propelled bacteria rotate in a plane. The separation distance between the bacteria determines the strength of the hydrodynamic coupling. Despite the noisy environment and autonomous dynamics of the living bacteria, we find evidence of phase locking and frequency entrainment in their rotation. The observation of higher order frequency synchronization is also discussed.